2021
DOI: 10.3390/ijms22126211
|View full text |Cite
|
Sign up to set email alerts
|

Role of JAK/STAT in Interstitial Lung Diseases; Molecular and Cellular Mechanisms

Abstract: Interstitial lung diseases (ILDs) comprise different fibrotic lung disorders characterized by cellular proliferation, interstitial inflammation, and fibrosis. The JAK/STAT molecular pathway is activated under the interaction of a broad number of profibrotic/pro-inflammatory cytokines, such as IL-6, IL-11, and IL-13, among others, which are increased in different ILDs. Similarly, several growth factors over-expressed in ILDs, such as platelet-derived growth factor (PDGF), transforming growth factor β1 (TGF-β1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
108
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(112 citation statements)
references
References 160 publications
1
108
0
3
Order By: Relevance
“…Moreover, IL-6 triggers JAK/STAT signaling, driving the transcription of an extensive range of acute phase proteins such as CRP. Furthermore, IL-6 may activate and promote differentiation or proliferation of several non-immune cells, including fibroblasts [37,38]. The application of combined therapeutic regimens against COVID-19-related SRF is an emerging challenge against this complex and heterogeneous mechanistic basis of COVID-19 pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, IL-6 triggers JAK/STAT signaling, driving the transcription of an extensive range of acute phase proteins such as CRP. Furthermore, IL-6 may activate and promote differentiation or proliferation of several non-immune cells, including fibroblasts [37,38]. The application of combined therapeutic regimens against COVID-19-related SRF is an emerging challenge against this complex and heterogeneous mechanistic basis of COVID-19 pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-6 triggers JAK/STAT signaling, driving the transcription of an extensive range of acute phase proteins such as CRP. Furthermore, IL-6 may activate and promote differentiation or proliferation of several non-immune cells, including fibroblasts [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Janus kinase 2 (JAK2) is an essential member of the non-receptor tyrosine kinase family, promoting the phosphorylation of signal transducer of activators of transcription 3 (STAT3). The activated STAT3 can enter the nucleus and participate in cell growth, differentiation, and apoptosis by regulating the expression of downstream target genes ( Montero et al, 2021 ). Growing evidence has shown that JAK2/STAT3 pathway plays a vital role in the pathogenesis of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin enters the nucleus and polymerizes with T cell factors and lymphocyte enhancer factors (TCF/LEF) to form intranuclear complexes, which regulate transcription of target genes and ultimately accelerate the progression of fibrosis ( Wang et al, 2018 ; Schunk et al, 2021 ). In addition to the above-mentioned pathways, Raf/MEK/ERK, JAK/STAT and other pathways are also involved in the regulation of fibrosis ( Figure 2 ; Guo et al, 2018 ; Foglia et al, 2019 ; Liu et al, 2019a ; Pompili et al, 2019 ; Montero et al, 2021 ). Fibrous diseases reportedly cause up to 45% of deaths in the western developed country ( Oruqaj et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%